RESILLIENT LIVING BY OPTIMIZING THE BUILDING FAÇADE IN DESIGNING POST-COVID HOUSING - Mohd Husini, Elina; Arabi, Fadli; Shamri, Shaza Liyana; Abdul Manaf, Azhani; Mat Idris, Madihah; Jamaludin, Juliza (PLANNING MALAYSIA, 2022)
The living performance in sustainable development outline contributing factors towards efficiency, such as ecological, economic, health, and social integration. The performance of facade design must be emphasised to describe resilient living and access to mitigate the design of post-coronavirus disease (COVID-19) housing. The spread of the pandemic underlines the importance of providing quality of life and wellbeing in the building environment, hence highlighting a crucial need to improve indoor air quality and passive building performance to minimise the transmission of COVID-19 and indoor airborne diseases as a result of poor ventilation. The passive building performance and facade complement the energy demand and reduce heat gain. Currently, passive design and health are emphasised to link the environmental design approach and architecture and highlight the quality-of-life post-pandemic. The study aims to provide important healthy indoor strategies and passive building performance for open-plan home-office design, to investigate the open-plan home design with optimum thermal performance based on the passive indoor environment, and to examine the bioclimatic response and energy efficiency of home-office design during the pandemic. The responsiveness of bioclimatic and modular construction incorporated with the new home-office design aim to save energy through sustainable material. The Integrated Environmental Solutions Virtual Environment (IESVE) computer software was utilised using simulations involving ranges of illuminance levels in daylight and revealed the acceptable levels of between 300 lux to 500 lux for the home office area. The results demonstrated that the optimum range of solar heat gain coefficient (SHGC) of 0.46 and a U-value of 0.04 W/m2 K reduced the indoor temperature by 5 degrees Celsius during peak time and maintained the air-condition at 28 degrees Celsius, which was within thermal comfort level.